Comparative Study Between Pre and Post Implementation of Several Policies: Air Quality Index in DKI Jakarta - Hilma Mutiara Winata; Agung Satrio Wicaksono (Jurnal Administrasi Publik, 2023)
Air quality in DKI Jakarta is currently trending. On August 10, 2023, Jakarta was ranked as the city with the worst air quality in the world. This condition causes a lot of anxiety among the public and disrupts health. Therefore, people in the capital city are asking the government to act quickly and precisely to overcome the problem of poor air quality. The response given by the government to deal with air pollution in DKI Jakarta is to provide several policies. Starting from August 11 until the end of August 2023, the government will issue up to 7 policies that are expected to overcome the pollution problem in the capital city. This research wants to see whether there is a difference in air quality in DKI Jakarta before and after the follow-up provided by the government. Daily recorded air quality index data is taken from a database, namely AQAIR. The data obtained was analyzed using the Mann-Whitney Test to see whether there were differences before and after the government issued the policy. After analyzing the data, the results showed that there was not sufficient evidence to state that there were significant differences related to air quality in DKI Jakarta before and after the policy issued by the government. Based on this, it seems that the policies issued by the government to overcome pollution are still not enough or not appropriate. Therefore, other alternative solutions are needed so that air quality problems can be resolved as soon as possible.